Legal Compliance of Islamic Philanthropic Institutions in Fulfilment of Children's Needs - Abdullah, Muh Ruslan; Osman, Zaiton; Fasiha, Fasiha; Ridwan, Muhammad Saleh (DIKTUM: Jurnal Syariah dan Hukum, 2023)
The management of the Orphanage that does not obey the law results in the Orphanage being unable to meet the needs of food, drink, education, health and Safety. Meanwhile, the Orphanage is an action-oriented charity that doesn't just collect orphans and abandoned children. The problem of managing the Orphanage has become a worldwide concern because many research results have found that the Orphanage does not carry out child development activities and that the orphanage children experience criminal acts. This study aims to reveal orphanage managers' legal compliance in meeting the foster children's needs. This study uses a descriptive legal analysis method, field data sourced from empirical studies at a philanthropic institution, namely the Orphanage in Palopo, totalling eight institutions. Data analysis was carried out with a legal approach. Data were collected through observation and in-depth interviews. The study found legal compliance in meeting the needs of facilities, food, education and health; security looks very good at orphanages managed by religious, community or boarding school-based organisations, while the lack of legal compliance in meeting the needs of orphanages that are managed at home or individually because only meet the needs of housing and food. The lack of legal compliance that occurs in home-based orphanages is due to a lack of management resources, including funds, lack of government participation in coaching and supervision.